ACEH BERDUKA (Analisis Program pemberitaan i-News TV malam) - Hanafi . (Universitas Informatika dan Bisnis Indonesia, 2020)
This research uses a critical discourse analysis method, from Fair Clough and the value of Islamic communication which not only analyzes the literature discourse but also describes the aspects of description, analysis, and interpretation of the overall coverage. The results of the study provide an explanation of the interpretation of the coverage of i-News TV evening, titled